An early investigation into raised-line tactile graphics reading behavior among blind and visually impaired individuals - Muhammad Ikmal Hakim Shamsul Bahrin,; Hazlina Md Yusof,; Shahrul Na’im Sidek,; Aimi Shazwani Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2024)
It has always been a challenge for blind and visually impaired (BVI) people to comprehend the information on tactile graphics materials. Despite the advancements in tactile graphic design, a comprehensive understanding of how they explore and interpret raised-line tactile graphics is still lacking. To bridge this gap, this paper introduces a fingertip tracking system employing color marker detection algorithm to investigate the cognitive process of four totally blind participants associated with the Malaysian Association for The Blind (MAB). Each participant was provided with five distinct kinds of raised-line tactile graphics for reading, and their reading activities were afterwards recorded. All participants exhibited diverse interpretations, exploration times, and difficulty perceptions, showcasing the subjective nature of cognitive processing. It is identified that the complex diagram took longer time of exploration with an average time of 141 seconds compared the simple diagram with an average time of 27.5 seconds. It shows that the complexity of the diagrams did impact participants’ cognitive process. Based on the distribution and concentration of fingertip locations, every tactile graphic has salient regions that have been focused on by every participant for recognition and interpretation of the information. It was also identified that the frequently performed exploratory procedures among participants were contour following and lateral motions. However, their reading strategies were too random and lacked systematic patterns. The system aims to be an instrument for visualising the cognitive process underpinning the exploration and interpretation of tactile graphics by people with visual impairment and blindness.